The Lockean Law of Restitution: How Lockean Justice Entails Significant Property Redistribution. (March 2021) - Jarrett, David
This article argues—in contrast to the claims of right-libertarians—that the Lockean thesis of justice in property seems to entail much egalitarian property redistribution. It starts by outlining what the Lockean thesis of justice in property is. It then argues that a Lockean version of the law of restitution is a reasonable way to approach the problem of holdings which were not gained in line with Lockean justice. Furthermore, according to this law, property which has unknown rightful owners should ideally be redistributed in an egalitarian manner among everybody in the world. In addition, due to the history of Lockean injustice throughout the world (e.g., feudalism and colonialism), it appears that much property in the world should be redistributed in an egalitarian manner.